The Law of Taking Talak Outside The Court in The Perspective of Maqashid Al-Syariah - Rofiq, Nur (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Research problems: What is the maqashid al-syariah perspective regarding someone who gives divorce outside the court? Research purposes: knowing the losses (mafsadat) due to divorce outside of court from the perspective of maqashid al-syariah. Research methods; using normative legal research (library research). Research results show that Divorce outside a court session is not permitted from a maqashid al-syariah perspective, even though it is permitted according to the Qur'an and hadith. Still, both imply indirectly that Islam allows divorce but, on the other hand, hopes that divorce will not occur. Divorce outside of court can disturb children's mental health. Children who were originally in a harmonious and loving family are suddenly in a family environment that is the opposite; their children are also feared to be vulnerable to falling into the company of alcohol and illegal drugs; the status of children is unclear according to the lawn causing the court to have no legal power to force the ex-husband to provide maintenance to the ex-wife during the iddah period; shelter, clothing, food and to their children too.